Effects of Increasing Standardized Ileal Digestible Lysine on Growth Performance of 40- to 90-Pound DNA Pigs - Rafe Q. Royall; Robert D. Goodband; Mike D. Tokach; Joel M. DeRouchey; Jordan T. Gebhardt; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this study was to estimate the SID Lys requirement for growth and feed efficiency of 40- to 90-lb DNA pigs. A total of 300 pigs (600 × 241, DNA; initially 40.6 ± 1.11 lb) were used in a 24-d trial. Pens of pigs were blocked by BW and randomly allotted to 1 of 6 dietary treatments with 5 pigs per pen and 10 pens per treatment in a randomized complete block design. Dietary treatments were corn-soybean meal-based and formulated to contain 1.00, 1.10, 1.20, 1.30, 1.40, and 1.50% SID Lys. Increasing SID Lys increased (linear,P= 0.003) ADG, decreased (linear,P= 0.012) ADFI, and improved (linear,P<0.001) feed efficiency. While these responses were linear, the greatest improvement in growth performance was observed as SID Lys increased from 1.00 to 1.10%. Although increasing SID Lys further slightly improved performance, the change was not great enough to economically justify feeding greater than 1.10% SID Lys. The quadratic polynomial model to maximize ADG predicted the maximum growth at 1.41% SID Lys. For F/G, the broken-line linear model predicted no further improvement past 1.35% SID Lys, while a similar fitting quadratic polynomial model predicted the optimum feed efficiency beyond the highest tested level of SID Lys. Additionally, the broken-line linear model for income over feed cost (IOFC) predicted maximum economic return at or below 1.12% SID Lys. In summary, the optimal SID Lys level for DNA pigs from 40 to 90 lb depends upon the response criteria, with growth performance maximized between 1.35 and>1.50% SID Lys; however, economic responses were maximized at or below 1.12% SID Lys.
Keywords: amino acid; growth; lysine requirement; grow-finish pig